Addressing organ shortage: are nudges the way forward?. (3rd July 2015) - Farrell, Anne-Maree
ABSTRACT: This paper examines the use of nudges in organ donation, against a background of organ shortage. This is a complex and contested area of public policy where questions of legitimacy loom large. The legitimacy of nudges is assessed by reference to function, values-based and democratic criteria. Analysis of normative claims made about nudges revealed that such criteria were not fulfilled. Findings from UK experimental studies showed that nudge interventions had a short-term effect, limited to increasing organ donation registration rates. It was unclear how this might translate into donation of organs after death or successful organ transplants. One of the studies also revealed the importance attached to reciprocity in motivating people to register as organ donors. This calls into question whether there should more of a focus on developing a reciprocity model to encourage human tissue donation, rather than relying on altruistic intent as embodied in the gift relationship.